Pelatihan Pajak Penghasilan (PPh) Pasal 21/26 - Febrianti, Meiriska; Sumarta, Rian; Njit, Tjhai Fung; Ponziani, Regi Muzio; Soegijanto, Cleophila M.G.T; Nisa, Shella Khoirun (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
This community service activity aimed to enhance students’ understanding of Income Tax (PPh) Articles 21 and 26 as well as their calculation in accordance with the latest regulations. The training was conducted on January 15, 2025, at SMK Pelita IV Jakarta and attended by approximately 180 students from various majors. The method of implementation included lectures, case studies, and interactive discussions led by qualified tax practitioners. The materials covered the legal basis of Articles 21 and 26, taxable and non-taxable income, withholding agents and recipients, taxpayers’ obligations, tax calculation based on Article 17 rates, and the application of the Monthly Effective Rate (TER). The results revealed that participants were able to understand fundamental taxation concepts, distinguish income components, and calculate Income Tax systematically. Moreover, the activity fostered awareness of the importance of tax compliance from an early age, equipping students with applicable tax literacy for their future careers. Therefore, this training successfully improved participants’ taxation competence and contributed to developing a young generation that is tax-conscious and compliant with Indonesia’s taxation regulations.